Ilmu al-Lughah al-Nafsiyah fi Manhaj Ta'lim al-Lughah al-'Arabiyyah fi 'Ashri ma Ba'da al-Thariqah - Muhammad Yusuf (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2019)
This paper aims to present the theory of psycholinguistics as a basis for developing the methodology of learning Arabic in the postmethods era. This paper relies on bibliographic sources in the form of books and articles (literature studies) that are in scientific journals related to the subject matter. Reading the data of thought by academics using a critical constructive approach and meaning of the substance using content analysis. Based on the studies that have been conducted, in the context of postmethods, psycholinguistic theory is seen as a building that is used as a foundation in developing learning models. Where in this era is marked by the reduction of the role of methods in language learning. The learning model that was born based on this assumption is an active learning model, cooperative learning, and (pakem) learning. Furthermore, in applying this model, the teacher is required to play an optimal role. The integral form, the teacher is required to have personal competence, social competence, and professional competence.